Contribucion al conocimiento de los dermestidae (Coleoptera) de Chile - Hava, J.=700 1 Solervicens, J.
(Es, En)
Ilus., 7 ref.
Keywords: COLEOPTERA; DERMESTIDAE; INSECTA; TAXONOMIA; ESPECIES NUEVAS; REGISTRO; CHILE